Impact of a training program on the basics of shadow teacher’s work in improvement resource room teacher’s knowledge A semi-experimental study in Hama - شروف انساب (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The current research aimed to prepare a training program on the basics of shadow teacher’s work in inclusive school, and to measure its impact on the resource room teacher’s knowledge in Hama. The semi-experimental approach was followed and a cognitive test prepared y he researcher was used in the pre/post measurements. The research sample consisted of (14) teacher working in resource room in the inclusive schools in Hama governorate, they were chosen who intentionally in condition (a less had two years old as a teacher in the resource room). The training program consisted of six training unites, completed in 30 training hours, during six days. The results of the research revealed the existence of a large impact size of (0.91) of the program in developing the level of the sample’s knowledge in the basics of shadow teacher’s work. The researcher suggested generalizing the program and applying it on other sample such as teachers and families.